Religious Self-Designating Behaviors. - McPhail, Clark (Journal for the Scientific Study of Religion (Wiley-Blackwell))
A theoretical and empirical problem of continuing attention is that of the origins and presentations of self, selling behaviors, or self-designating behaviors. Research is reported examining the origins and presentations of religious sell-designations given by a national sample of the United States adult population. Twenty-seven percent of the sample responded to the question "Who Am I?" with religious self-designations. Three interpretations of self-designations are examined: reference group theory; attitude theory; and a derivation of Mead's social behaviorism theory. Respondents self-selected "most important groups," "religious beliefs," and "religious activity participation are examined for association with sell-designations. Moderate support is provided for the social behaviorism account of the origins and presentations of religious sell-designations.